Personal Information Management (PIM) dalam Proses Belajar Siswa Disabilitas Netra Tingkat SMP dan SMA Swasta di Surabaya - Salsabila, Afnan Rizqiana; Mutia, Fitri; Yuwinanto, Helmy Prasetyo (BACA: Jurnal Dokumentasi dan Informasi, 2025)
The need for information to support the learning process is increasingly becoming a challenge for students with visual disabilities. They actively seek and use various sources of information, which causes information overload and affects the way they manage information in the future. This research uses Personal Information Management (PIM) theory which includes three main activities: finding/refinding, keeping, and the meta-level using a quantitative descriptive approach involving 32 respondents. The aim of this research is to understand how students with visual disabilities at private junior and senior high schools in Surabaya manage information in their learning process. The results show that, in finding/refinding activities, the majority of students (88%) need additional information related to subject matter accessed via the internet (91%). In keeping activities, students tend to save information on WhatsApp via the message yourself feature (81%). At the-level, the majority of students (91%) prioritize the privacy and security of their academic information. They also often separate relevant information from irrelevant (63%), although not yet effectively. Obstacles faced include device and screen reader problems (84%), as well as the tendency of students to forget where their information is stored (80%). However, 53% of students feel that the information management strategies they apply can support their daily learning activities.